THE EFFECT OF AFFILIATE MARKETING AND INFLUENCER CREDIBILITY ON CONSUMER ENGAGEMENT IN INDONESIAN E-COMMERCE - Ummi Fisabilillah; Amri Dunan (Journal Informatic, Education and Management (JIEM), 2026)
This study examines the influence of affiliate marketing strategies on the level of consumer involvement in online transactions in the Indonesian e-commerce industry. To determine the influence of consumer credibility on the level of consumer involvement in online transactions in the Indonesian e-commerce industry. To determine the influence of affiliate marketing strategies and consumer credibility on the level of consumer involvement in online transactions in the Indonesian e-commerce industry. The research method uses quantitative. Data collection uses a questionnaire, SPSS data processing. The results of the study on the Influence of Affiliate Marketing Strategies and Influencer Credibility on the Level of Consumer Involvement in Online Transactions in Indonesian E-Commerce can be concluded as follows: The Sig. value for affiliate marketing (X1) on consumer involvement (Y) is 0.00 <0.05 and the t-value is 5.905> t-table 1.984. So there is a partial influence of affiliate marketing (X1) on consumer involvement (Y). The Sig. value. The correlation between influencer credibility (X2) and consumer engagement (Y) was 0.00 < 0.05, with a calculated t value of 6.026 > ttable value of 1.984. This indicates that influencer credibility (X2) partially influences consumer engagement (Y). The significance value for the influence of affiliate marketing and influencer credibility on consumer engagement was 0.00 < 0.05, with an Fcount value of 158.882 > Ftable value of 3.090. This indicates that affiliate marketing and influencer credibility are accepted, indicating a simultaneous influence of affiliate marketing and influencer credibility on consumer engagement. Affiliate marketing and influencer credibility influence consumer engagement by 76.3%. The remaining 23.7% is influenced by other factors not examined.